Edukasi Strategi Mencapai Berkah Sehat Menjelang Masa Purna Pada Pegawai Bank Syariah Indonesia Lhokseumawe - Maulina Debbyousha; Khairunnisa, Cut; Nur Fardian; Ridhalul Ikhsan; Noviana Zara; M. Hafizd Fadhri (Academica : Jurnal Pengabdian Kepada Masyarakat, 2024)
Entering retirement age or the golden years is a process marking the end of regular work and the beginning of rest, as active working years have come to a close. Special preparation is necessary to face this period so that each individual can maintain and improve their quality of life This commitment is carried out with the aim of providing education to employees of Bank Syariah Indonesia Lhokseumawe regarding the blessings of health as they approach retirement The education provided emphasizes the importance of maintaining health through adopting a balanced and nutritious diet, engaging in proper and regular physical activity and exercise, and quitting smoking Improving quality of life also requires effective stress management and personal hygiene Regular health check-ups are also necessary to detect any potential health issues early on.